Adolescent health problems and strategies to improve them - Dara, Sanjeeta; Arora, Smriti (International Journal Of Community Medicine And Public Health, 2023)
Adolescent as any person between ages 10 and 19. It is a transitional stage of physical, physiological and psychological development from puberty to legal adulthood. The data about important adolescent’s health issues in different areas are limited. Hence detailed investigation and reports on adolescent’s health issues is the need of the hour. To achieve wholesome adolescent health, we need to have a multidimensional approach covering all the adolescent health problems with special emphasis on mental health, behavior change communication towards healthy lifestyle and positive social environment to acquire life skills. Availability of good quality care and healthcare workers trained to deal with adolescents is critical for delivering effective health interventions. Providing health care to adolescents presents a dual challenge: the treatment of immediate health problems, and the opportunity through health promotion and disease prevention, to influence health habits, lifestyle choices, and health status in adulthood because health behaviors originating in adolescence may well have long term health consequences.